Aspects of the Cultural Concept of [Peace] in English and Polish: An Ethnolinguistic Account - Gicala Agnieszka (Studies in Logic, Grammar and Rhetoric)
The paper aims to analyse how native speakers of English and Polish understand one of the basic cultural concepts: English PEACE and Polish POKÓJ. By juxtaposing the current understanding of these concepts with the data recorded in dictionaries, an attempt is made to catch a glimpse of what is meant by peace in English and pokój in Polish and, what follows, to reflect on them in terms of translation and intercultural communication. The study was inspired by elements of the methodology developed by the Lublin School of Ethnolinguistics for the purpose of research into cultural concepts and constructing their cognitive definitions. In particular, my analysis begins with a textual illustration that prompts the research direction, in which etymology as well as unique connotations recorded by the survey respondents are granted as much significance as the dictionary material, with attention paid to the dimension of metonymy and metaphor in the analysed cultural concepts of PEACE and POKÓJ. Comparing and contrasting the core meanings with their current shifts and extensions is aimed to help embed words in their broader linguacultural context and thus shed some light on aspects of intercultural communication, operationalised via translation.